2018
DOI: 10.1016/j.compedu.2018.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of community of inquiry framework in regard to self-regulation, metacognition and motivation

Abstract: I hereby declare that all information in this document has been obtained and presented in accordance with academic rules and ethical conduct. I also declare that, as required by these rules and conduct, I have fully cited and referenced all material and results that are not original to this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 124 publications
(219 reference statements)
3
53
0
2
Order By: Relevance
“…Also, when compared to Moodle, which is a less user-friendly environment, Facebook could be expected to be favored by the students. This might improve students' social presence (Kilis & Yildirim, 2018). The other issue is that some previous empirical findings indicated that Facebook is an effective discussion Design and organization Facilitating discourse Direct instruction environment in online and/or blended learning (English & Duncan-Howell, 2008;Mazer, Murphy, & Simonds, 2007).…”
Section: Social Presencementioning
confidence: 99%
“…Also, when compared to Moodle, which is a less user-friendly environment, Facebook could be expected to be favored by the students. This might improve students' social presence (Kilis & Yildirim, 2018). The other issue is that some previous empirical findings indicated that Facebook is an effective discussion Design and organization Facilitating discourse Direct instruction environment in online and/or blended learning (English & Duncan-Howell, 2008;Mazer, Murphy, & Simonds, 2007).…”
Section: Social Presencementioning
confidence: 99%
“…The Community of Inquiry (CoI) theoretical framework informs this research (Garrison, Anderson, & Archer, 2001). This framework, comprised of domains for teaching, social and cognitive presence, suggests high-quality online education is realized when learners interact socially and coordinate efforts with peers, link new knowledge to past understanding, and directly apply the information to their present lives in a learning environment that places great importance on self-reflection and selfregulated learning (Garrison, 2007;Kilis & Yıldırım, 2018;Shea & Bidjerano, 2010).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Kilis & Yildirim [7] state that metacognition has been discussed around the concept of self-regulation. Lajoie [8] states that the concept of metacognition is intertwined with the concepts of self-regulation and self-regulated learning, and is often used interchangeably in the literature.…”
Section: Introductionmentioning
confidence: 99%